Case Report: Uncommon presentation of Ewing sarcoma complicated by hemophagocytic lymphohistiocytosis: a diagnostic dilemma and therapeutic challenge - Zou, Zhuan; Chen, Bin; Tang, Fajuan; Li, Xihong; Huang, Chengshuang (Frontiers in Oncology, 2025)
Hemophagocytic lymphohistiocytosis (HLH), also referred to as hemophagocytic syndrome (HPS), is a life-threatening condition characterized by excessive immune activation. It is commonly associated with genetic mutations, infections, autoimmune diseases, and malignancies. Malignancy-associated HLH (M-HLH) is most frequently observed in hematologic malignancies, such as lymphoma and leukemia, while its occurrence in solid tumors is exceedingly rare. Here, we report a unique case of temporal bone Ewing sarcoma complicated by HLH and Epstein-Barr virus (EBV) infection. Despite intensive chemotherapy, the patient ultimately succumbed to multi-organ failure and septic shock. To the best of our knowledge, this is the first documented case of Ewing sarcoma associated with HLH.